Marine-Derived Fungi in Korea - Kwon, Yong Min; Bae, Seung Sub; Choi, Grace; Lim, Ji Yeon; Jung, Yoon-Hee; Chung, Dawoon (Ocean science journal, 2021)
Studies on marine fungi (termed as ‘marine-derived fungi’ in this paper) have been significantly increasing worldwide because of the critical role displayed by marine fungi in the marine ecosystem and their potential as sources of bioactive compounds. Korea is surrounded by three seas containing abundant marine resources. In this review, to facilitate research and applications of marine fungi, we summarized previously studied marine fungi in Korea focusing on published research articles in peer-reviewed journals over the last two decades. Approximately 79% of the studies (66 articles) were published in the 2010s and described a total of 818 strains (isolates) of 266 species belonging to 3 phyla, 8 classes, 21 orders, 43 families, and 76 genera. The most prevalent fungi belong to the genera Penicillium / Eupenicillium / Talaromyces , accounting for 40.2% of all species (107 species), followed by Aspergillus / Eurotium / Neosartorya (13.9%, 37 strains). Approximately 67% of fungal strains were originated from the eastern (44.6%, 365 strains) and western coasts (22.1%, 181 strains), and their main isolation sources were coastal plants/halophytes, marine animals, sediment, and marine algae. More than 35% of the strains (292 strains) produced novel and/or bioactive compounds with enzymatic, antimicrobial, antioxidant, anti-cancer, anti-inflammatory, anti-diabetic, or multi-functional activities. This review provides insights into current knowledge and future perspectives regarding marine-derived fungi in Korea.